2010
DOI: 10.1111/j.1542-4758.2010.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma myeloperoxidase, NT‐proBNP, and troponin‐I in patients on CAPD compared with those on regular hemodialysis

Abstract: Myeloperoxidase (MPO) is a hemoprotein that is released during inflammation and may lead to irreversible protein and lipid modification, increasing levels of oxidized low density lipoprotein, and promoting athrogenesis. Recently, it has been considered as a risk factor for cardiovascular diseases. Similarly, the measurement of carotid intima-media thickness gives an indication about the degree of atherosclerosis and prediction of clinical cardiovascular events. Elevated white blood cells counts may indicate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Our results clearly show that patients on HD are more likely to have elevated levels of NT-proBNP compared to patients on CAPD, and this finding may suggest that from the cardiovascular stand point CAPD is a better alternative to HD for renal replacement therapy. These data are consistent with previously mentioned studies [27][28][29] . Whether an advantage predicted by a marker such as NT-proBNP leads to an actual morbidity or mortality benefit cannot be determined from the present study, and this clinically relevant hypothesis warrants further investigation.…”
Section: Abnormal Nt-probnp In Hd Vs Capdsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results clearly show that patients on HD are more likely to have elevated levels of NT-proBNP compared to patients on CAPD, and this finding may suggest that from the cardiovascular stand point CAPD is a better alternative to HD for renal replacement therapy. These data are consistent with previously mentioned studies [27][28][29] . Whether an advantage predicted by a marker such as NT-proBNP leads to an actual morbidity or mortality benefit cannot be determined from the present study, and this clinically relevant hypothesis warrants further investigation.…”
Section: Abnormal Nt-probnp In Hd Vs Capdsupporting
confidence: 83%
“…The thought that such volume shifts would have adverse effect on the cardiovascular system have been postulated before, and there is an accumulating body of evidence suggesting that BNP and NT-proBNP levels are higher among patients on HD (ref. [27][28][29][30]. No previous studies to our knowledge assessed NT-proBNP according to the level of preservation of the left ventricular systolic function.…”
Section: Abnormal Nt-probnp In Hd Vs Capdmentioning
confidence: 99%
“…The disulfide/native thiol levels were also different between the three groups; the disulfide/native thiol levels were slightly higher in the transplantation and PD groups compared to the HD group. While these results are consistent with few other previous studies, increased levels of oxidative stress in HD compared to those in PD have also been reported in some studies (20)(21)(22)(23)(24). We believe that the increased oxidative stress observed in the PD patients (compared to those in the HD patients) in our study may have been caused by inflammatory responses.…”
Section: Discussionsupporting
confidence: 54%
“…Also, it is not known whether oxidative stress varies with dialysis modality. In a few studies, increased levels of oxidative stress have been reported to be associated with hemodialysis (HD) compared with peritoneal dialysis (PD) (18,19), but other studies showed the opposite results (20)(21)(22).…”
mentioning
confidence: 99%